In silico analysis and identification of promising hits against 2019 novel coronavirus 3C-like main protease enzyme. Issue 14 (22nd September 2021) - Chatterjee, Shilpa; Maity, Arindam; Chowdhury, Suchana; Islam, Md Ataul; Muttinini, Ravi K.; Sen, Debanjan
Abstract: The recent outbreak of the 2019 novel coronavirus disease (COVID-19) has been proved as a global threat. No particular drug or vaccine has not yet been discovered which may act specifically against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and causes COVID-19. For this highly infectious virus, 3CL-like main protease (3CL pro ) plays a key role in the virus life cycle and can be considered as a pivotal drug target. Structure-based virtual screening of DrugBank database resulted in 20 hits against 3CL pro . Atomistic 100 ns molecular dynamics of five top hits and binding energy calculation analyses were performed for main protease-hit complexes. Among the top five hits, Nafarelin and Icatibant affirmed the binding energy (g_MMPBSA) of –712.94 kJ/mol and –851.74 kJ/mol, respectively. Based on binding energy and stability of protein-ligand complex; the present work reports these two drug-like hits against SARS-CoV-2 main protease. Communicated by Ramaswamy H. Sarma